Development of Interactive Learning Multimedia Based on Articulate Storyline in Mathematics for Grade VIII at SMP YPI Batumarta II - Sri Febriani; Yamanto Isa; Heni Rita Susila (Universitas Trunodjoyo Madura, 2026)
This study aims to develop interactive learning multimedia based on Articulate Storyline in mathematics for the topic of linear equations in one variable, which will be developed in Grade VIII of SMP YPI Batumarta II. The research method used is Research and Development (RD) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, expert validation questionnaires, and student response questionnaires. The developed product was validated by experts. Furthermore, the product was tested through individual trials involving three students, small group trials involving nine students, and field trials involving thirty-six students. The results of the study show that the Articulate Storyline-based interactive learning multimedia obtained a material expert validation result of 96.2% in the “very good” category, a learning design expert result of 83.7% in the “good” category, and a media expert result of 85.1% in the “good” category. The results of the individual trial obtained a percentage of 90.2%, the small group trial 87.3%, and the field trial 88.2%, all in the “very good” category. These results indicate that the Articulate Storyline-based interactive learning multimedia is easy to use, engaging, and helps students learn mathematics.